2008
DOI: 10.1080/02602930601125681
|View full text |Cite
|
Sign up to set email alerts
|

Judging quality through substantive conversations between markers

Abstract: Decisions by markers about quality in student work remain confusing to most students and markers. This may in part be due to the relatively subjective nature of what constitutes a quality response to an assessment task. This paper reports on an experiment that documented the process of decision-making by multiple markers at a university who assessed the same written student assessment responses. The paper analyses the professional conversations between those markers around their conceptions of quality in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2009
2009
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 7 publications
0
23
0
1
Order By: Relevance
“…Grades are signals of achievement and show students their areas of strength and weakness and can inform instructors about the success of their teaching (Joughin, 2009;Yorke, 2009;Brown, 2010;Walvoord and Anderson, 2011). Obviously, the quality of assessment matters so that inferences and decisions by students and instructors, as well as external stakeholders (e.g., employers), can be made on a robust basis (Grainger et al, 2008).…”
Section: Assessment In Higher Educationmentioning
confidence: 99%
“…Grades are signals of achievement and show students their areas of strength and weakness and can inform instructors about the success of their teaching (Joughin, 2009;Yorke, 2009;Brown, 2010;Walvoord and Anderson, 2011). Obviously, the quality of assessment matters so that inferences and decisions by students and instructors, as well as external stakeholders (e.g., employers), can be made on a robust basis (Grainger et al, 2008).…”
Section: Assessment In Higher Educationmentioning
confidence: 99%
“…For example, Van der Shaff (2011), Orr (2007 and Grainger et al (2008) have all adopted this approach and a key benefit is its implicit naturalness. In the study reported here the conversations were happening anyway which contrasts with Grainger et al's study where the conversations are elicited by the researcher through the creation of an assessment scenario.…”
Section: Using Recorded Conversationsmentioning
confidence: 99%
“…As a result we rejected the use of (quasi) experimental approaches where assessments are set up for the sole purpose of research. Grainger et al (2008) adopted a quasi experimental approach in a study where they asked multiple markers to assess the same pieces of student work. In their study the data consisted of the transcripts of the 'professional conversations' about the work.…”
Section: Aim Of Studymentioning
confidence: 99%
“…Whilst unreliability in academics' assessment of student work is welldocumented, there is little prior data indicating how much specific criteria are interpreted differently although similar evidence was found by Grainger, Purnell and Zipf (2008). This is worthy of further investigation given the emphasis placed on analytical criteria in many qualification frameworks, lists of threshold outcomes and professional standards.…”
Section: Discussionmentioning
confidence: 94%